Migraine Prevalence and Use of Preventive Therapy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2007)
The epidemiology of migraine in the United States, and the patterns of migraine treatment in the population were assessed and contrasted with current treatment recommendations in a study at Albert Einstein College of Medicine and Montefiore Headache Center, Bronx, NY; The New England Center for Headache, Stamford, CT; Diamond Headache Center, Chicago, IL; Vedanta Research, Chapel Hill, NC; and Geisinger Clinic, Danville, PA.